Some notes on the experience of the Teatro Nuevo XX and its scenographic proposal (Rosario, 1942‒1947) (El Taco en la Brea, 2024)
The text proposes to reconstruct aspects linked to the conformation and development of the Teatro Nuevo XX in the city of Rosario, founded and directed by the Buenos Aires playwright Alberto Rodríguez Muñoz. In the context of the innovations deployed by independent theaters at a national and international level, between 1942 and 1947 Muñoz's company carried out an aesthetic proposal linked to the idea of social transformation, in which different plastic artists and designers from the city participated. making the scenery, decorations, clothing and staging. The work investigates the beginnings of this theatrical training, its foundations, characteristics and aesthetic and ideological assumptions, as well as Muñoz's perspective on theater and set design, reported in different publications of the time. We will also refer to the interventions of Ricardo Warecki, who integrated the experience from its beginnings, reaffirming the links between the plastic arts and modern theater.
Keywords: independent theater; Alberto Rodríguez Muñoz; Ricardo Warecki; plastic arts; scenography